Enhanced Catalytic Properties of Carbon supported Zirconia and Sulfated Zirconia for the Green Synthesis of Benzodiazepines. Issue 22 (30th October 2018) - Godino‐Ojer, Marina; Milla‐Diez, Leticia; Matos, Inês; Durán‐Valle, Carlos J.; Bernardo, Maria; Fonseca, Isabel M.; Pérez Mayoral, Elena
Abstract: This work reports for the first time a new series of promising porous catalytic carbon materials, functionalized with Lewis and Brønsted acid sites useful in the green synthesis of 2, 3‐dihydro‐1 H ‐1, 5‐benzodiazepine – nitrogen heterocyclic compounds. Benzodiazepines and derivatives are fine chemicals exhibiting interesting therapeutic properties. Carbon materials have been barely investigated in the synthesis of this type of compounds. Two commercial carbon materials were selected exhibiting different textural properties: i) Norit RX3 (N) as microporous sample and ii) mesoporous xerogel (X), both used as supports of ZrO2 (Zr) and ZrO2 /SO4 2− (SZr). The supported SZr led to higher conversion values and selectivities to the target benzodiazepine. Both chemical and textural properties influenced significantly the catalytic performance. Particularly relevant are the results concerning the non‐sulfated samples, NZr and XZr, that were able to catalyze the reaction leading to the target benzodiazepine with high selectivity (up to 80 %; 2 h). These results indicated an important role of the carbon own surface functional groups, avoiding the use of H2 SO4 . Even very low amounts of SZr supported on carbon reveal high activity and selectivity. Therefore, the carbon materials herein reported can be considered an efficient and sustainable alternative bifunctional catalysts for the benzodiazepine synthesis. Abstract : Paint it black : This work reports a new series of porous catalytic carbon materials, functionalized with Lewis and Brønsted acid centers, active in the green synthesis of 2, 3‐dihydro‐1H‐1, 5‐benzodiazepine. The studies demonstrated that both the carbon porous structure and acid site types are involved in the reaction. The texture and composition of the investigated carbon materials strongly influenced the catalytic performance.